Quality of life and post-traumatic stress symptoms in paediatric patients with tibial fractures during treatment with cast or Ilizarov frame. Issue 2 (February 2020) - Johnson, L.; Messner, J.; Igoe, E.J.; Foster, P.; Harwood, P.
Highlights: No significant difference was found in health-related quality of life during treatment between patients treated using a cast or an Ilizarov frame. Polytrauma, mechanism of injury and time from injury were identified as significant predictors of quality of life scores. Polytrauma, mechanism of injury and time from injury were identified as significant predictors of severity of posttraumatic stress symptoms. Abstract: Purpose: To compare quality of life in children and adolescents with tibial fracture during treatment with either a definitive long-leg cast or Ilizarov frame. Methods: A prospective, longitudinal cohort study was undertaken. Patients aged between 5 and 17 years with tibial fractures treated definitively using a long-leg cast or Ilizarov frame were recruited at first follow-up. Health related quality of life was measured at each clinic appointment during treatment using the Pediatric Quality of Life Inventory (PedsQL) [1] ; a validated measure of age-adjusted physical and psychosocial functioning. Psychological trauma symptoms were assessed using the Children's Revised Impact of Events Scale (CRIES) [2] . Results were analysed based on time from injury (less than 30 days, 30 to 120 days). Data regarding injury and treatment was recorded from the clinical records. Statistical analysis was undertaken using a Kruksal–Wallis test with a Tukey–Kramer subgroup analysis. Results: Twenty-five patients from each group were included in the final analysis. Injuries were more severe in the frame patients based on the AO/OTA classification and number of open fractures. No statistically significant differences were detected in any of the outcome scores between treatment groups at either time point. A significant improvement was found in the child reported physical and total domains in both treatment groups based on time from application (<30 days vs. >30 days, frame: p  < 0.0001, cast: p  = 0.003). There were no differences in the child reported psychosocial domain scores at any time point or between treatment groups. Parent reported scores only showed a significant physical improvement in the frame group ( p  < 0.0001). CRIES scores for psychological trauma in the intrusion and avoidance domain improved significantly in the cast group between time points ( p  < 0.05), Multivariate analysis identified polytrauma, mechanism of injury and time from injury but not treatment modality (cast or frame) as significant predictors of quality of life scores (PedsQL) and severity of post-traumatic symptoms (CRIES). Conclusion: We found no difference in health-related quality of life during treatment between our patients treated for tibial fractures using a cast or an Ilizarov frame.